An experimental study on ceramic design for reflexology tools / Zainatunhawa Amadudin - Amadudin, Zainatunhawa (Faculty of Education, 2014)
This paper discussed about creating a design of form for reflexology’s tool by using a ceramic method. For information, there are small numbers of reflexology tools that using ceramic as their medium. By using a ceramic, the tools should be functional as well as decorative, providing insulation and unbreakable. Moreover, the purpose of this research is to know about the characteristic and the effectiveness of using clay as a main medium to produce this product. The researcher has used two research methods. There are by primary data which is experimentation and observation and secondary data the additional facts which are obtained from sources such as books, academic books, journals, sources from the webs in the internet. The researcher has found that by using clay as a medium to produce a tool or a product is a usual way but in reflexology field it still a new way in this era. That becomes more interesting and successful when choosing a right design for reflexology tool. The body of that clay itself is strong enough and the processes of making ceramic product are challenging and took more time to produce it. The conclusion was done based on the finding. Due to the limitations of this research a few recommendations ware suggested.